Perioral reconstruction after Mohs micrographic surgery: analysis of 108 cases - Flávia Trevisan; Nataly Portilla Maya; Guilherme Canho Bittner; Bruno de Carvalho Fantini; Felipe Bochnia Cerci (Sociedade Brasileira de Dermatologia (SBD), 2021)
Introduction: The perioral region is commonly affected by non-melanoma skin cancer. Mohs micrographic surgery is the treatment of choice in this area because it has the highest cure rate and preserves healthy tissue. Several methods are available for restoring the perioral region, and their selection is influenced by the surgical wound characteristics and the surgeon's preference. Objective: Describe the authors' experience in perioral reconstruction after Mohs micrographic surgery and analyze the repair methods most frequently performed. Methods: Retrospective study of consecutive cases submitted to Mohs surgery and perioral reconstruction. Results: The study included 108 cases from 103 patients. The mean number of Mohs surgery stages was 1.4, and the mean defect size was 16 mm. Primary closure was the most used technique for reconstruction, followed by flaps (mainly V-Y, single advancement, and rotation). The association of repair methods was used in 28.7% of cases, mostly combined with flaps. Four patients had complications (necrosis and graft infection, trapdoor effect, and partial wound dehiscence). Conclusion: Primary closure was the most frequent repair method, followed by flaps. Knowing reconstruction strategies and possibilities of associations is essential for proper restoration of the perioral region, maintaining its function, sensation and aesthetics.